Recent attainments of research on plasma physics and technology AT IPJ, Poland - Sadowski, M.J. (Вопросы атомной науки и техники, 2008)
This invited lecture presents the most important achievements of the IPJ team in theoretical- and experimental-studies in the field of plasma physics and technology during recent years. The main efforts concentrated on the development of diagnostic techniques and studies of plasmas in Plasma-Focus (PF) facilities and Multi-Rod Plasma Injectors (RPI). Other efforts concerned diagnostics of fast electrons in selected Tokamaks (CASTOR, ISSTOK, and TORE-SUPRA), fusion protons in TEXTOR, and fusion neutrons in JET (EURATOM). Separate efforts concerned technological applications, e.g. modeling of an IPD accelerator for the material engineering, the use of UHV arc-discharges to deposit superconducting Nb layers on RF cavities and superconducting Pb photo-cathodes in electron injectors (EC CARE). Представлено найбільш важливі досягнення колективу ІЯП у теоретичних і експериментальних дослідженнях в області фізики плазми і технології за останні роки. Основні зусилля були сконцентровані на розробці діагностичної техніки і дослідженнях плазми в плазмових фокусах (ПФ) і багатострижневих плазмових інжекторах. Розвито діагностику швидких електронів на деяких токамаках (CASTOR, ISSTOK, й TORE-SUPRA), термоядерних протонів на TEXTOR та нейтронів синтезу на JET (ЄВРАТОМ). Технологічні прикладення включали моделювання ІПН прискорювача для матеріалознавства, використання надвисоковакуумних дугових розрядів для напилювання надпровідних Nb шарів на РЧ-резонатори і надпровідних Pb фотокатодів для інжекторів електронів (EC CARE). Представлены наиболее важные достижения коллектива ИЯП в теоретических и экспериментальных исследованиях в области физики плазмы и технологии за последние годы. Основные усилия были сконцентрированы на разработке диагностической техники и исследованиях плазмы в плазменных фокусах (ПФ) и многостержневых плазменных инжекторах. Развита диагностика быстрых электронов на некоторых токамаках (CASTOR, ISSTOK, и TORE-SUPRA), термоядерных протонов на TEXTOR и нейтронов синтеза на JET (ЕВРАТОМ). Технологические приложения включали моделирование ИПН ускорителя для материаловедения, использование сверхвысоковакуумных дуговых разрядов для напыления сверхпроводящих Nb слоев на РЧ- резонаторы и сверхпроводящих Pb фотокатодов для инжекторов электронов (EC CARE).